2007
DOI: 10.1093/jn/137.11.2405
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Reduces Blood Pressure in Hypertensive Subjects1,

Abstract: Epidemiological studies report that quercetin, an antioxidant flavonol found in apples, berries, and onions, is associated with reduced risk of coronary heart disease and stroke. Quercetin supplementation also reduces blood pressure in hypertensive rodents. The efficacy of quercetin supplementation to lower blood pressure in hypertensive humans has never been evaluated. We tested the hypothesis that quercetin supplementation reduces blood pressure in hypertensive patients. We then determined whether the antihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
316
3
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(348 citation statements)
references
References 41 publications
18
316
3
11
Order By: Relevance
“…A better knowledge of the cellular communication network (54) in warfarin-treated vascular cells will be instrumental in developing approaches to prevention and treatment of this disorder. Our results contribute to the mechanistic understanding of the beneficial effects of quercetin on cardiovascular disease (55,56) and expose ␤-catenin signaling as a novel major target for preventive therapy of warfarin-induced VC. In addition, our findings suggest that quercetin may be a promising therapeutic to test in preclinical models of elastocalcinosis taking into consideration the wide safety margin of quercetin (57), its broad testing in clinical trials, and its applicability as a daily dietary supplement.…”
Section: Discussionmentioning
confidence: 72%
“…A better knowledge of the cellular communication network (54) in warfarin-treated vascular cells will be instrumental in developing approaches to prevention and treatment of this disorder. Our results contribute to the mechanistic understanding of the beneficial effects of quercetin on cardiovascular disease (55,56) and expose ␤-catenin signaling as a novel major target for preventive therapy of warfarin-induced VC. In addition, our findings suggest that quercetin may be a promising therapeutic to test in preclinical models of elastocalcinosis taking into consideration the wide safety margin of quercetin (57), its broad testing in clinical trials, and its applicability as a daily dietary supplement.…”
Section: Discussionmentioning
confidence: 72%
“…Epidemiological studies, together with data from animal models and some clinical trials, suggest a role of dietary flavonoids in the prevention of CVD and other age-related chronic diseases (108)(109)(110) . The flavonol quercetin exhibits a wide range of physiological effects such as inhibition of LDL-oxidation, lowering of arterial blood pressure and platelet aggregation, and improvement of endothelial function as shown in animal models and in human subjects (111)(112)(113)(114)(115)(116)(117) . Furthermore, cell culture and animal studies indicate a potent anti-inflammatory activity of quercetin (116,(118)(119)(120) .…”
Section: Flavonoidsmentioning
confidence: 99%
“…Post-supplementation overnight-fasted plasma quercetin levels ranged between 0 and 899 mg/l for 95% of subjects, but no rationale was provided for this variation. Another human study (N ¼ 41) using quercetin aglycone supplements (730 mg quercetin/day for 28 days) (Edwards et al, 2007) showed that post-supplementation plasma quercetin concentrations (mean ± s.d.) for the placebo Pre-study 118 ± 9.0 86.0 ± 8.0 86.1 ± 6.5 (mg/l) Post-study 160±10.7 433±36.1* 674±64.9* w 40-59 years, n 140 141 145 Quercetin Pre-study 91.7 ± 6.4 84.7 ± 6.0 94.6 ± 6.2 (mg/l) Post-study 150 ± 8.6 394 ± 26.4* 533 ± 28.5* w 60-85 years, n 81 84 64 Quercetin Pre-study 98.5 ± 9.3 89.1 ± 8.2 85.2 ± 34.4 (mg/l) Post-study 161±11.9 439±55.0* 640±74.8* w BMI (kg/m 2 ) o25, n 152 157 138 Quercetin Pre-study 105 ± 6.6 88.7 ± 6.3 105 ± 6.8 (mg/l) Post-study 153 ± 8.5 439 ± 33.8* 593 ± 40.7* w 25-29.9, n 95 94 109 Quercetin Pre-study 105±9.3 75.7±6.5 74.8±5.9 (mg/l) Post-study 161±11.1 375±32.0* 611±59.6* w X30, n 86 81 83 Quercetin Pre-study 95.4 ± 9.4 93.6 ± 9.3 83.9 ± 8.5 (mg/l) Post-study 155 ± 11.7 427 ± 44.2* 617 ± 65.1* w Abbreviation: BMI, body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term quercetin supplementation, however, results in a highly variable plasma quercetin response, and little is known regarding the factors that explain this variance (Conquer et al, 1998;Erlund et al, 2000;Goldberg et al, 2003;Egert et al, 2008). In four different human trials, quercetin supplementation with doses of 8-1000 mg/day for 2-6 weeks resulted in overnightfasted plasma quercetin values with an unexpectedly wide inter-individual variation (Conquer et al, 1998;Erlund et al, 2000;Edwards et al, 2007;Egert et al, 2008). Edwards et al, for example, reported a 13-fold range in overnight-fasted plasma quercetin for two-thirds of 41 subjects after 4 weeks of supplementation with 730 mg quercetin per day.…”
Section: Introductionmentioning
confidence: 99%